2020
DOI: 10.1101/2020.08.26.265439
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Network asynchrony underlying increased broadband gamma power

Abstract: Synchronous activity of cortical inhibitory interneurons expressing parvalbumin (PV) underlies the expression of cortical gamma rhythms. Paradoxically, deficient PV inhibition is associated with increased broadband gamma power. Increased baseline broadband gamma is also a prominent characteristic in schizophrenia, and a hallmark of network alterations induced by N-methyl-D-aspartate receptor (NMDAR) antagonists such as ketamine. It has been questioned if enhanced broadband gamma power is a true rhythm, and if … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
18
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 76 publications
(36 reference statements)
5
18
0
Order By: Relevance
“…Optical pulsatile activation (30 Hz) of the ACC to VC projection resulted in decreases in low-frequency LFP power (consistent with a decrease in our Synch measure, Fig. 1h,i) and increases in high-frequency power (consistent with an increase in FR 44,45 ) in the visual cortex -akin to our favorable state for accuracy after errors. Inter-estingly, a behavioral effect of either excitation or suppression of this projection was only observed when the manipulation was performed in the baseline period after errors.…”
Section: Discussionsupporting
confidence: 74%
“…Optical pulsatile activation (30 Hz) of the ACC to VC projection resulted in decreases in low-frequency LFP power (consistent with a decrease in our Synch measure, Fig. 1h,i) and increases in high-frequency power (consistent with an increase in FR 44,45 ) in the visual cortex -akin to our favorable state for accuracy after errors. Inter-estingly, a behavioral effect of either excitation or suppression of this projection was only observed when the manipulation was performed in the baseline period after errors.…”
Section: Discussionsupporting
confidence: 74%
“…First, PV cells play a key role in generating and maintaining gamma oscillations in the brain 83,84 . In particular, recent studies have also shown that deficiency in PV interneuron-mediated inhibition contribute to increased baseline cortical gamma rhythm 79,85,86 , a phenotype we observed in both mutant mice and SYNGAP1-ID patients (Figure 2). Second, auditory habituation has been shown to involve an increase in inhibition 87,88 .…”
Section: Discussionsupporting
confidence: 66%
“…Contrary to the oscillatory narrow-band signals, such as alpha rhythm, broadband activity recorded with ECoG primarily reflects asynchronous neuronal firing (Buzsáki et al, 2012; Guyon et al, 2021; Henrie and Shapley, 2005; Hwang and Andersen, 2011; Li et al, 2019; Mukamel et al, 2005). Likewise, our earlier modeling of power-law changes in Broadband PCS suggests they reflect a change in mean population-averaged firing rate (Miller et al, 2009a; Miller, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, our earlier modeling of power-law changes in Broadband PCS suggests they reflect a change in mean population-averaged firing rate (Miller et al, 2009a; Miller, 2010). The association between broadband signals and neuronal spikes has been demonstrated both during passive tasks (Guyon et al, 2021; Manning et al, 2009) as well as in response to sensory stimulation (Henrie and Shapley, 2005; Hwang and Andersen, 2011; Li et al, 2019; Medvedev and Kanwal, 2004). While most of the evidence comes from visual neuroscience (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation